A game theoretic approach to implementation of recycled drinking water. Issue 51 (1st November 2016) - Qian, Neng; Leong, Ching
Abstract: Singapore is known as a successful example of implementing recycled drinking water (NEWater) policy. Acceptance of recycled water could be seen as a new social norm (NEWater norm). We first use a discourse analysis to investigate people's perception on recycled drinking water. Such perceptions incorporate psychological disgust ("yuck" factor) as well as social concerns (water security, economic incentives, long-term sustainability). Based on these perceptions, game theory approach is applied to analyze the emergence and evolutionary process of the NEWater norm. We find that, a "thick" perception on recycled drinking water entails the possibility of new norm formation; in such an environment, acceptance of NEWater will gradually penetrate into the whole population from an even small portion of leaders.